Relationship between FDI inflow, CO2 emissions, renewable energy consumption, and population health quality in China - Zhang, Ziwei; Nuță, Florian Marcel; Dimen, Levente; Ullah, Irfan; Xuanye, Si; Junchen, Yao; Yihan, Zhou; Yi, Chen (Frontiers in Environmental Science, 2023)
China has received significant foreign direct investment in the last few decades; the FDI inflow could affect the environment, income, and people’s health. Therefore, this paper aims to investigate the relationship between FDI, renewable energy consumption, CO2 emissions, and Population health quality in China for the period 1980–2020. We applied the VECM method for the data analysis for the short and long-run effects of the independent variables. In the short run, FDI and CO2 emissions did not affect health quality in China; however, in the long run, FDI and CO2 emissions improved life expectancy. Renewable energy has both run and long implications for the health quality in China. These results reflect that FDI creates more jobs in China and improves the overall income of Chinese citizens, contributing to more accessible healthcare services in the long run. Therefore, the government should provide incentives to increase the FDI inflow, which uses renewable energy in production. Furthermore, to mitigate the CO2 emissions government should implement a carbon tax on the industries which has substantial CO2 emissions in the country.